Simultaneous targeting of Tim3 and A2a receptors modulates MSLN-CAR T cell antitumor function in a human cervical tumor xenograft model - Soltantoyeh, Tahereh; Akbari, Behnia; Shahosseini, Zahra; Mirzaei, Hamid Reza; Hadjati, Jamshid (Frontiers in Immunology, 2024)
Introduction Chimeric antigen receptor (CAR) T cell therapy has transformed the treatment of hematological malignancies. However, its efficacy in solid tumors is limited by the immunosuppressive tumor microenvironment that compromises CAR T cell antitumor function in clinical settings. To overcome this challenge, researchers have investigated the potential of inhibiting specific immune checkpoint receptors, including A2aR (Adenosine A2 Receptor) and Tim3 (T cell immunoglobulin and mucin domain-containing protein 3), to enhance CAR T cell function. In this study, we evaluated the impact of genetic targeting of Tim3 and A2a receptors on the antitumor function of human mesothelin-specific CAR T cells (MSLN-CAR) in vitro and in vivo. Methods Second-generation anti-mesothelin CAR T cells were produced using standard cellular and molecular techniques. A2aR-knockdown and/or Tim3- knockdown anti-mesothelin-CAR T cells were generated using shRNA-mediated gene silencing. The antitumor function of CAR T cells was evaluated by measuring cytokine production, proliferation, and cytotoxicity in vitro through coculture with cervical cancer cells (HeLa cell line). To evaluate in vivo antitumor efficacy of manufactured CAR T cells, tumor growth and mouse survival were monitored in a human cervical cancer xenograft model. Results In vitro experiments demonstrated that knockdown of A2aR alone or in combination with Tim3 significantly improved CAR T cell proliferation, cytokine production, and cytotoxicity in presence of tumor cells in an antigen-specific manner. Furthermore, in the humanized xenograft model, both double knockdown CAR T cells and control CAR T cells could effectively control tumor growth. However, single knockdown CAR T cells were associated with reduced survival in mice Conclusion These findings highlight the potential of concomitant genetic targeting of Tim3 and A2a receptors to augment the efficacy of CAR T cell therapy in solid tumors. Nevertheless, caution should be exercised in light of our observation of decreased survival in mice treated with single knockdown MSLN-CAR T cells, emphasizing the need for careful efficacy considerations.